Analysing the use of an interactive data visualization in order to disseminate detailed data on rail fatalities - Wronska, Urszula (2016)
The subject of this Dissertation is the design of an interactive data visualization to disseminate the findings of the research related to rail fatalities to stakeholders within the Rail Industry. The design process consisted of three main stages which were: development of requirements, design and evaluation. The process of the development of requirements built upon the analysis of given datasets and the study findings, the analysis of examples of data visualization used in the rail industry, the review of literature reporting findings on the geographical factors that may influence the occurrence of incidents and the semi-structured interviews with representatives of stakeholders groups. The main goal identified in this process was to provide information about the suicides that occurred on the stations in the context of geographical factors in the area that might influence the occurrence of the events. Interactive data was designed, based on the set of requirements and the principles for data visualization. A prototype illustrating the main functions of the system was produced. In the process of evaluation, the prototype was presented to the representatives of stakeholders groups and feedback on the design was gathered through the use of an on-line questionnaire. All of the participants agreed that the application highlights key features of the data and that the use of this tool has the potential to improve the understanding of the factors that may influence the occurrence of incidents.